2019
DOI: 10.16965/ijar.2019.202
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Variations of Brachial Artery in Cadavers

Abstract: Background: The study of brachial artery is an important arterial conduit from the clinical point of view to anatomists, general surgeons, radiologists, plastic surgeons, and even cardiovascular thoracic surgeons in the conduct of reparative surgery.Therefore, the present study was designed to study the course, branching pattern and termination of Brachial Artery and its clinical significance of these variations. Materials and Methods:The present study was conducted on 30 upperlimbs of 15 cadavers embalmed & b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…In India, 30 specimens were dissected, then it was reported that the brachial artery in the third middle part gives a branch. The accessory brachial artery was in one case (3.3%) among the 30 limbs, then trifurcation of the brachial artery was also seen in 1 case (3.3%) into Radial Artery, Ulnar Artery, Common interosseous Artery [10], which is different from the current case where the Brachial artery bifurcated in the proximal third of the arm. Jacomo et al in 2014 in São Paulo and Eyni in 2016 reported similar cases in which the Brachial artery bifurcation was observed in the proximal portion of the middle third of the arm, forming lateral and medial branches.…”
Section: Discussioncontrasting
confidence: 73%
“…In India, 30 specimens were dissected, then it was reported that the brachial artery in the third middle part gives a branch. The accessory brachial artery was in one case (3.3%) among the 30 limbs, then trifurcation of the brachial artery was also seen in 1 case (3.3%) into Radial Artery, Ulnar Artery, Common interosseous Artery [10], which is different from the current case where the Brachial artery bifurcated in the proximal third of the arm. Jacomo et al in 2014 in São Paulo and Eyni in 2016 reported similar cases in which the Brachial artery bifurcation was observed in the proximal portion of the middle third of the arm, forming lateral and medial branches.…”
Section: Discussioncontrasting
confidence: 73%
“…Other variations related to brachial artery reported are duplications, superficial brachial artery, accessory brachial artery, dilated tortuous brachial artery and trifurcations. 2,18 These variations may have occurred due to multiple plexiform sources, crossed haemodynamic predominance between primitive deep and superficial arterial segments and regression of arterial segments that have minor haemodynamic significance. 2 Such unexpected variations during routine clinical and surgical procedure may cause hazards.…”
Section: Resultsmentioning
confidence: 99%
“…The superficial radial artery may be mistaken for vein causing reflex vascular occlusion by accidental cannulation resulting in risk of gangrene. 18 A case was reported where brachial artery was explored for acute arterial insufficiency of right upper limb. Residual embolus at high bifurcating point of brachial artery was detected and thrombectomy of high originating ulnar artery was done.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the arm, it is superficial in its course and gives off the following branches; profunda brachii which is the largest branch and supplies triceps brachii, superior and inferior ulnar collateral (SUC&IUC) arteries, muscular branches to supply muscles of anterior compartment of the arm i.e., biceps brachii, coracobrachialis and brachialis, nutrient artery to the humerus, and terminates into the ulnar and radial arteries. (George et al, 2019;Gupta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%